Análisis técnico legal de la institución jurídica de la servidumbre de tránsito, y su aplicabilidad en el sector rural. - Morales Coloma, Joffre Kevin (2023)
XIV It is necessary to consider that the information obtained in this study is an indication of how real and harmful the actions that prevent the healthy enjoyment of the inherent rights of each person can be. KEYWORDS: TRANSIT EASEMENT, RIGHT, DOMINANT PROPERTY, SERVIENT ESTATE, ENCUMBRANCE, BENEFIT.